Innovative Seismic Response-Controlled System with Shear Wall and Concentrated Dampers in Lower Stories - Tani, Tsubasa; Maseki, Ryota; Takewaki, Izuru (Frontiers in Built Environment, 2017)
A new structural control system using damper-installed shear-walls in lower stories with reduced stiffness is proposed for vibration control of high-rise RC buildings. That system has some design variables, i.e. height of shear-wall, degree of stiffness reduction at lower stories, and quantity of dampers. In this paper, some parametric studies on the shear-beam model with a stiff beam against two kinds of ground motion, a pulse-type sinusoidal wave and a resonant sinusoidal wave, are conducted to clarify the vibration characteristics of the proposed structural control system. It is shown that the optimal combination of design parameters depends on the input ground motion. It is also shown that it is possible to prevent from increasing the response under the one-cycle sinusoidal input resonant to the lowest mode and reduce the steady-state response under the harmonic input with the resonant fundamental period by reducing the stiffness in the lower structure and increasing the damper deformation.